Development and evaluation of a mechanical ventilator-sharing system - Achanta, Satyanarayana; Gentile, Michael A.; Euliano, Neil R. (Frontiers in Medicine, 2024)
Background During the COVID-19 pandemic surge in the hospitalization of critically ill patients and the global demand for mechanical ventilators, alternative strategies for device sharing were explored. We developed and assessed the performance of a system for shared ventilation that uses clinically available components to individualize tidal volumes under a variety of clinically relevant conditions. The feasibility of remote monitoring of ventilators was also assessed. Methods By using existing resources and off-the-shelf components, a ventilator-sharing system (VSS) that ventilates 2 patients simultaneously with a single device, and a ventilator monitoring system (VMS) that remotely monitors pulmonary mechanics were developed. The feasibility and effectiveness of VSS and VMS were evaluated in benchtop testing using 2 test lungs on a single ventilator, and then performance was assessed in translational swine models of normal and impaired lung function. Results In benchtop testing, VSS and VMS delivered the set individualized parameters with minimal % errors in test lungs under pressure- and volume-regulated ventilation modes, suggesting the highest precision and accuracy. In animal studies, the VSS and VMS successfully delivered the individualized mechanical ventilation parameters within clinically acceptable limits. Further, we found no statistically significant difference between the target and measured values. Conclusion The VSS adequately ventilated 2 test lungs or animals with variable lung conditions. The VMS accurately displayed mechanical ventilation settings, parameters, and alarms. Both of these systems could be rapidly assembled for scaling up to ventilate several critically ill patients in a pandemic or mass casualty disaster situations by leveraging off-the-shelf and custom 3D printed components.